2010
DOI: 10.1016/j.quaint.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A post Younger Dryas Black Sea regression identified from sequence stratigraphy correlated to core analysis and dating

Abstract: The north-western Black Sea shelf is the widest continental shelf of the Black Sea, where the Danube delta/prodelta system includes important records on the Black Sea water level fluctuations. This study integrates newly acquired high-resolution single channel seismic reflection profiles and Calypso piston cores recovered along a transect extending from the Danube delta deep into its deep sea fan. The correlated results provide information on the Late Quaternary architecture of the Danube Black Sea shelf and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…This is possible in contexts where the rates of sea level rise and sediment supply overwhelm the sediment dispersion rates of the currents (Davis and Clifton, 1987). This interpretation is in agreement with the "cliff overstep" model proposed by Zecchin et al (2011) for steep shelves where relative high sea level rise connected to the Meltwater pulses promotes a rapid drowning of cliff portions with related rapid excursion of the shoreline; and with the documentations of the high sediment supply recorded on the Mediterranean shelves during the Younger Dryas interval (e.g., Labaune et al, 2005;Berné et al, 2007;Lericolais et al, 2010;Maselli et al, 2011;Sømme et al, 2011). The further jump in sea level highlighted by the subsequent landward migration of the uTST unit depocenter (Fig.…”
Section: The Main Factors Favored the Pgcd Preservationsupporting
confidence: 89%
See 1 more Smart Citation
“…This is possible in contexts where the rates of sea level rise and sediment supply overwhelm the sediment dispersion rates of the currents (Davis and Clifton, 1987). This interpretation is in agreement with the "cliff overstep" model proposed by Zecchin et al (2011) for steep shelves where relative high sea level rise connected to the Meltwater pulses promotes a rapid drowning of cliff portions with related rapid excursion of the shoreline; and with the documentations of the high sediment supply recorded on the Mediterranean shelves during the Younger Dryas interval (e.g., Labaune et al, 2005;Berné et al, 2007;Lericolais et al, 2010;Maselli et al, 2011;Sømme et al, 2011). The further jump in sea level highlighted by the subsequent landward migration of the uTST unit depocenter (Fig.…”
Section: The Main Factors Favored the Pgcd Preservationsupporting
confidence: 89%
“…The lower and upper TST units (lTST and uTST unit, respectively) record an abrupt landward shift of the shoreline, while the middle unit (mTST unit) is prograding seaward and represents a regressive sedimentary body within the TST (Cattaneo and Trincardi, 1999). The three TST units are separated by two prominent, and extensively erosional, surfaces (S1 and S2 surface, Cattaneo and Trincardi, 1999; Jouet et al, 2006;Sømme et al, 2011;Chiocci et al, 1991;Lykousis et al, 2005;Aksu et al, 2002;Giosan et al, 2009;Lericolais et al, 2010;Schattner et al, 2010;Zecchin et al, 2011;Durán et al, 2013) and highstand clinothemes (green patches; Díaz and Ercilla, 1993;Lobo et al, 2006;Fanget et al, 2014;Cattaneo et al, 2007;Hiscott et al, 2002;Giosan et al, 2013). (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
Section: Stratigraphic Setting Of Adriatic Tst Depositsmentioning
confidence: 99%
“…At that time, the water level was controlled by regional climate and varied independently from global sea level (Ross et al, 1970). Based on seismic stratigraphy (Ryan et al, 1997;Winguth et al, 2000;Aksu et al, 2002;Lericolais et al, 2009Lericolais et al, , 2010Lericolais et al, , 2011 and reservoir age reconstructions (Soulet et al, 2011a), it is suggested that the water level of the Black Sea 'Lake' oscillated from ca − 150/− 100 m (e.g., during the LGM) to ca. − 35/− 25 m, that corresponds to the depth of the Bosphorus sill.…”
Section: Climate and Water-level Fluctuations In The Black Sea Duringmentioning
confidence: 99%
“…Therefore it makes unlikely the Black Sea to have kept low stage in the Early Holocene. Even if this lowstand had been really occurring, it could hardly be governed by river runoff decrease as it was proposed in (Lericolais et al, 2010).…”
Section: Discussion and Final Remarksmentioning
confidence: 96%
“…According to Lericolais et al (2010), in the period 13.0-9.5 ka cal BP (11.0-8.5 ka 14 C BP) the Black Sea exhibited regression and low stand, which was followed by rapid ultimate transgression starting immediately after ~9.5 ka cal BP (8.5 ka 14 C BP). According to our results, the Upper Dnieper River had high discharges since the very beginning of the Holocene till about 8 ka cal BP.…”
Section: Discussion and Final Remarksmentioning
confidence: 99%